Dampak Environmental Disclosure dan Kinerja Keuangan terhadap Reaksi Investor - Rahmawati, Iroh (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2025)
The relationship between environmental issues, financial performance, and investment decisions is increasingly becoming a focus in the business and financial world, especially with the increasing awareness of global environmental issues such as climate change. Investors and companies increasingly recognize that integrating environmental factors into business and investment strategies can create better and more sustainable long-term value. The purpose of this study was to determine the impact of environmental disclosure and financial performance on investor reactions. The research method used was multiple linear regression. The results of this study indicate that environmental disclosure and financial performance have a simultaneous effect on investor reactions of 0.7336 or 73.36%.